2016
DOI: 10.1017/s1041610216000818
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous temporal trends in dementia incidence and prevalence, 2005–2013: a population-based retrospective cohort study in Saskatchewan, Canada

Abstract: Background:Original studies published over the last decade regarding time trends in dementia report mixed results. The aims of the present study were to use linked administrative health data for the province of Saskatchewan for the period 2005/2006 to 2012/2013 to: (1) examine simultaneous temporal trends in annual age-and sex-specific dementia incidence and prevalence among individuals aged 45 and older, and (2) stratify the changes in incidence over time by database of identification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
39
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 44 publications
6
39
1
Order By: Relevance
“…In the United States, studies have shown either a relatively stable or declining age-adjusted prevalence of dementia and cognitive impairment in the past 3–4 decades [ 32, 34, 50 ]. In Canada, an increased age-standardized prevalence of dementia was reported, along with a decline in incidence, which suggests that the survival of patients with dementia may have improved over time [ 33 ].…”
Section: Time Trends In Occurrence Of Dementiamentioning
confidence: 99%
See 1 more Smart Citation
“…In the United States, studies have shown either a relatively stable or declining age-adjusted prevalence of dementia and cognitive impairment in the past 3–4 decades [ 32, 34, 50 ]. In Canada, an increased age-standardized prevalence of dementia was reported, along with a decline in incidence, which suggests that the survival of patients with dementia may have improved over time [ 33 ].…”
Section: Time Trends In Occurrence Of Dementiamentioning
confidence: 99%
“…While the time trends in the prevalence of dementia over time are determined by trends in the incidence of dementia and the duration of the disease, the secular trends in the incidence of dementia could indicate whether the risk of late-life dementia is modifiable. Several community-based studies in Europe (e.g., the Netherlands, France, Germany, and the UK) have shown that the incidence of dementia has been declining in the past 2–4 decades [ 33, 42, 44, 48, 50, 54–64 ] ( Table 3 ). For instance, the Rotterdam Study reported a 25% decrease, though statistically marginal, in the incidence of all-cause dementia between 1990 and 2000 in people aged 55+ years [ 60 ].…”
Section: Time Trends In Occurrence Of Dementiamentioning
confidence: 99%
“…The Alzheimer’s Association recently concluded that, even though the incidence of AD has been decreasing, its prevalence has been increasing over the past 25 years in the U.S. [6]; another study projected that the number of people with AD will triple by 2050 [7]. A recent Canadian [8] retrospective cohort study found a simultaneous trend of decreasing incidence and increasing prevalence of dementia over a relatively short 8-year time period from 2005/06 to 2012/13, with the age-standardized prevalence increasing from 21.35% to 27.87%. Other studies also demonstrated increases in dementia prevalence in UK [9], another Canadian study [10], and pooled European data [11] (also reviewed in [12]).…”
Section: Introductionmentioning
confidence: 99%
“…(Dodge et al ., 2016; Kosteniuk et al ., 2016). These reports join the ranks of a growing body of literature on generational trends, or more, specifically, “cohort effects,” in aging, cognitive decline, and dementia.…”
mentioning
confidence: 99%
“…Kostenyuk and colleagues (2016) examined administrative health databases for the Canadian province of Saskatchewan over eight years and found a significant decrease in the incidence of dementia with a simultaneous increase in the prevalence of dementia. This seeming paradox has a simple explanation.…”
mentioning
confidence: 99%